2009
DOI: 10.1039/b822635k
|View full text |Cite
|
Sign up to set email alerts
|

Probing the microscopic hydrophobicity of smectite surfaces. A vibrational spectroscopic study of dibenzo-p-dioxin sorption to smectite

Abstract: The interaction of dibenzo-p-dioxin (DD), from aqueous suspension, with smectite was investigated using in situ vibrational spectroscopy (FTIR and Raman), structural and batch sorption techniques. Batch sorption isotherms were integrated with in situ attenuated total reflectance (ATR)-FTIR and Raman spectroscopy and X-ray diffraction. Sorption isotherms revealed that the affinity of DD for smectite in aqueous suspension was strongly influenced both by the type of smectite and by the nature of the exchangeable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 44 publications
(74 reference statements)
2
54
0
Order By: Relevance
“…61 This is especially evident for Cs + -exchanged saponite. 54,55 The use of K-saponite was included in this study to evaluate the role of mineral-only surfaces. Although significant, the overall sorption affinity of DD for K-saponite is several orders of magnitude less than that for DODA–SWy-2 or GAC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…61 This is especially evident for Cs + -exchanged saponite. 54,55 The use of K-saponite was included in this study to evaluate the role of mineral-only surfaces. Although significant, the overall sorption affinity of DD for K-saponite is several orders of magnitude less than that for DODA–SWy-2 or GAC.…”
Section: Resultsmentioning
confidence: 99%
“…Physicochemical details about this clay have been reported previously. 5254 The clay was exchanged with Na + by placing 40 g of the clay in 1 dm 3 of 0.5 M NaCl for 24 h. The resulting Na–smectite suspension was “washed” with 0.5 M NaCl twice. Excess salts were removed by repeated centrifugation with Millipore water until a negative Cl − test using AgNO 3 was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher extent of isomorphic substitution in tetrahedral layers of NAu2, results in stronger localized charge on the clay surface with respect to SWy1. Rana et al (2009) suggested that localized charge leaves more "charge-neutral" siloxane surfaces that are not influenced directly by isomorphic substitutions. In nontronite these sites may be more favorable for hydrophobic interactions.…”
Section: Adsorption Of Cutin Monomers By Claysmentioning
confidence: 99%
“…One of the most useful ways to study molecular adsorption onto talc (and other minerals/particles) is to use the methodology of particle film attenuated total reflection (ATR) FTIR spectroscopy. [36][37][38][39][40][41][42] The detection of polymer adsorbing from a dilute solution onto a thin (sub-micron thickness) layer of mineral particles on top of an ATR crystal allows direct determination of important parameters such as adsorption kinetics and polymer binding mechanisms. [43][44][45][46] The data presented below for PNIPAM on talc reveal information of the polymer conformation at the mineral surface, the rapidity of adsorption, tendency for desorption, and an inference of the most likely binding mechanism for the polymer-mineral interaction.…”
Section: Introductionmentioning
confidence: 99%